On the relationship between the environmental history and the epidemiological situation of Argentine hemorrhagic fever - Polop, Francisco Jose (2007)
The aim of this work was to establish the relationship between diﬀerent Argentine hemorrhagic fever (AHF) epidemiological situations found at diﬀerent sites and the related large-scale environmental conditions. Large-scale environmental records (vegetation index, temperature, precipitation and elevation) were obtained from a series of monthly NOAA satellite images and global databases considered suitable for modeling climatic and other environmental determinants of large-scale biogeographical regions. The temporal variation in vegetation for cycles of winter-summer showed a greater variation in the nonendemic region than in the other two regions. On the other hand, the average of the temporal variation in precipitation in cycles of spring–autumn was more diﬀerent in the historic region than in the other two regions, and land surface temperatures in cycles of spring–autumn showed diﬀerences between the epidemic region and the other two regions. We found good separation among the epidemic, historic and nonendemic sites, with the greatest diﬀerence found between epidemic and nonendemic sites. The classiﬁcation of sites showed a tendency for grouping according to the epidemiological situation, but there was some variation. It seems possible to establish a close relationship between the state of AHF incidence and the environmental history of sites suggesting the possibility of predicting epidemiological behavior using environmental conditions derived from satellite data.